Katalog der in den Sammlungen der Abteilung Taxonomie der Insekten des Institutes für Pflanzenschutzforschung, Bereich Eberswalde (ehemals Deutsches Entomologisches Institut), aufbewahrten Typen - XV (Coleoptera: Hydrophilidae). - Döbler, Helga (Contributions to Entomology = Beiträge zur Entomologie, 1977)
The types of the family Hydrophilidae of Coleoptera in the collections of the Department of Taxonomy of Insects of the Institute of Plant Protection Research, Eberswalde (former Deutsches Entomologisches Institut) are listed, and data on first descriptions and existing type material are given.